Predictors of bone mineral density testing among older women on Medicare. Issue 12 (December 2016) - Lou, Y.; Edmonds, S.; Jones, M.; Ullrich, F.; Wehby, G.; Cram, P.; Wolinsky, F.
Abstract Summary Although dual-energy X-ray absorptiometry (DXA) is recommended for all women ≥65 and is covered by Medicare, 40 % of women on Medicare report never having had a DXA. In a longitudinal cohort of 3492 women followed for two decades, we identified several risk factors that should be targeted to improve DXA testing rates. Introduction DXA is used to measure bone mineral density, screen for osteoporosis, and assess fracture risk. DXA is recommended for all women ≥65 years old. Although Medicare covers DXA every 24 months for women, about 40 % report never having had a DXA test, and little is known from prospective cohort studies about which subgroups of women have low use rates and should be targeted for interventions. Our objective was to identify predictors of DXA use in a nationally representative cohort of women on Medicare. Methods We used baseline and biennial follow-up survey data (1993–2012) for 3492 women ≥70 years old from the nationally representative closed cohort known as the Survey on Assets and Health Dynamics among the Oldest Old (AHEAD). The survey data for these women were then linked to their Medicare claims (1991–2012), yielding 17, 345 person years of observation. DXA tests were identified from the Medicare claims, and Cox proportional hazard regression models were used with both fixed and time-dependent predictors from the survey interviews including demographic characteristics, socioeconomic factors, health status, health habits, and the living environment. Results DXA use was positively associated with being Hispanic American, better cognition, higher income, having arthritis, using other preventative services, and living in Florida or other southern states. DXA use was negatively associated with age, being African-American, being overweight or obese, having mobility limitations, and smoking. Conclusions Interventions to increase DXA use should target the characteristics that were observed here to be negatively associated with such screening.